Proceedings of the 17th ACM Conference on Interaction Design and Children 2018
DOI: 10.1145/3202185.3210781
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for family-centered health management

Abstract: Blood and marrow transplantation (BMT) is an intensive therapy for patients with life-threatening hematologic cancer as well as non-cancer diagnoses. Children, adolescents and young adults undergoing BMT ("pediatric patients") experience intensive medical procedures during their treatment and post-treatment recovery phases. We conducted a field study to identify common barriers that interfere with pediatric patient engagement in the management of their health and challenges that caregivers confront. Our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This study identified a significant cognitive and time burden for family caregivers of CSHCN to share complete information accurately and concisely regarding their child’s health with other caregivers [ 40 - 42 ]. Information sharing occurs within caregiver handoffs in the home, at caregiver team meetings in clinics and schools, and with their child’s physicians and specialists [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study identified a significant cognitive and time burden for family caregivers of CSHCN to share complete information accurately and concisely regarding their child’s health with other caregivers [ 40 - 42 ]. Information sharing occurs within caregiver handoffs in the home, at caregiver team meetings in clinics and schools, and with their child’s physicians and specialists [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the cognitive burden that family caregivers face in accurately sharing information with others, digital tools should support caregivers to access information efficiently and effectively depending on with whom they are interacting and their current working environment. For example, in the clinical setting, design recommendations for digital health technology development to support health care management of pediatric blood marrow transplant patients have been described by Shin et al [ 42 ]. Although not explicitly describing how the user would interact with the technology to access insights about the health data, their results similarly point toward the idea of a digital health tool that provides general use in tracking patient symptoms, consult visits, and medications, supporting the caregiver’s cognitive load to remember details accurately [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies in HCI and healthcare domain highlight the scope and the benefits of available technology-mediated interventions designed for children and their families specifically in health [13]. These interventions range from family-centered health management [11] to health information delivery [7]. Studies have revealed that shared responsibility and support among family members have positive impacts on illness management [10].…”
Section: Background and Related Studymentioning
confidence: 99%